Finite Element Analysis of Reinforced Concrete Coupling Beams - Bambang Boediono; Nyoman Triani Herlina Dewi; Erwin Lim (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
The use of reinforced concrete coupling beams in high-rise buildings is popular, especially in seismic prone areas. The modeling of a reinforced concrete coupling beam in a commercial structural analysis software is usually simplified to a line element or a compound of concrete and steel rebar as fiber element. Hence, the analysis of the simplified model cannot capture the overall hysteretic behavior of the element. Moreover, the simplified model is also limited in its capacity to estimate the shear strength contributed by the concrete and diagonal bars, if any, respectively. This study used an advanced finite element analysis package to simulate the cyclic behavior of four coupling beam specimens available in the database. The results show that the hysteretic loop predicted by the finite element analysis tends to overestimate the maximum lateral load capacity. On the other hand, analytical evaluation of the shear strength contributed by concrete and diagonal bars showed good agreement with the test results.